Correlation and path coefficient analysis in chilli (Capsicum annuum L.) based on yield and yield related traits (Research in Agriculture Livestock and Fisheries, 2024)
An experiment was carried out in the field laboratory of the Department of Genetics and Plant Breeding of Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Gazipur during the period from October 2018 to April 2019. The experiment was set up in a randomized complete block design (RCBD) and three replications were used. The aim of the study was to assess the character association and direct and indirect effect of independent characters on green yield of 28 chilli genotypes. A comparison between genotypic and phenotypic correlation coefficients revealed that the former was higher. At both the genotypic and phenotypic levels, correlation coefficients revealed that fruit yield per plant was significantly and positively linked with fruit length, fruit diameter, individual fruit weight, number of seeds per fruit, and plant height. Individual fruit weight had the most significant positive direct impact on fruit yield, followed by the number of fruits per plant, fruit diameter, and fruit length. Therefore, these characteristics could be regarded as critical selection criteria for the enhancement of chilli yield.Res. Agric. Livest. Fish. Vol. 11, No. 2, August 2024: 231-238